2015
DOI: 10.1007/s00428-015-1836-2
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin alteration is rare in hepatocellular carcinoma with steatohepatitic features: immunohistochemical and mutational study

Abstract: Hepatocellular carcinoma (HCC) with steatohepatitic features (steatohepatitic HCC, SH-HCC) is a histological subset of HCC, highly associated with metabolic disease and underlying steatohepatitis. Although it has distinct clinicopathologic characteristics, little is known about the immunophenotype or genetic characteristics of SH-HCC. We conducted an immunohistochemical analysis on a tissue microarray containing 197 HCCs (70 SH-HCCs and 127 conventional HCCs (C-HCCs)), focusing on proteins associated with gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 35 publications
3
49
1
Order By: Relevance
“…employed a Food and Drug Administration (FDA)‐approved diagnostic platform (Elements assay; NanoString Technologies, Seattle, WA, USA) to correlate clinicopathological features and molecular subclasses of HCC, and showed that 57.9% of steatohepatitic HCC harboured molecular signatures of the subclass S1 . HCC of the molecular subclass S1 is characterized by Wnt and TGF‐β activation, larger tumour, poorer differentiation and early tumour relapse, all of which oppose to features of steatotic and steatohepatitic HCC documented by us and others: rare β‐catenin activation, smaller tumour, better differentiation and late tumour relapse. The pathogenesis of steatotic HCC and steatohepatitic HCC remains inconclusive, and warrants additional studies.…”
Section: Discussionmentioning
confidence: 97%
“…employed a Food and Drug Administration (FDA)‐approved diagnostic platform (Elements assay; NanoString Technologies, Seattle, WA, USA) to correlate clinicopathological features and molecular subclasses of HCC, and showed that 57.9% of steatohepatitic HCC harboured molecular signatures of the subclass S1 . HCC of the molecular subclass S1 is characterized by Wnt and TGF‐β activation, larger tumour, poorer differentiation and early tumour relapse, all of which oppose to features of steatotic and steatohepatitic HCC documented by us and others: rare β‐catenin activation, smaller tumour, better differentiation and late tumour relapse. The pathogenesis of steatotic HCC and steatohepatitic HCC remains inconclusive, and warrants additional studies.…”
Section: Discussionmentioning
confidence: 97%
“…They hypothesized that deregulation of the Wnt/β‐catenin pathway had a minor role in the development of this type of HCC . Ando and colleagues are also found that β‐catenin alteration is rare in SH‐HCC . Given that obesity is associated with chronic low‐grade systemic inflammation, these results are quite acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…92 Moreover, SH-HCC patients reportedly have a relatively good prognosis. 100 These characteristics are similar to steatotic sHCC, but SH-HCC and steatotic sHCC are not the same, because fibrous stroma is not a necessary criterion for SH-HCC. 97,98 Because there is some overlap in steatotic sHCC and SH-HCC, further investigation is required to clarify the differences between these two subtypes.…”
Section: Fibrous Stroma In Hccmentioning
confidence: 96%
“…Low nuclear accumulation of β‐catenin and low expression levels of GS, SALL4 and EpCAM have been reported in SH‐HCC, and a recent study revealed that SH‐HCC was associated with the G4 subclasss . Moreover, SH‐HCC patients reportedly have a relatively good prognosis . These characteristics are similar to steatotic sHCC, but SH‐HCC and steatotic sHCC are not the same, because fibrous stroma is not a necessary criterion for SH‐HCC .…”
Section: The Hcc Tumor Microenvironmentmentioning
confidence: 99%